Pengaruh Pendidikan Kesehatan Gigi dan Mulut terhadap Perilaku Orangtua dalam Memelihara Kesehatan Gigi dan Mulut Anak - Alfiyah Pujiyati; Risya Cilmiaty; Widia Susanti; Betty Saptiwi; Adi Priyatno (Faculty of Dentistry Universitas Andalas, 2022)
Background: The high prevalence of dental caries in preschool children is caused by various factors, including: knowledge, attitudes and behavior of parents. Preschoolers (93%) were included in severe early caries (dmf-t 8.43). Objective: To determine the effect of dental health education on parents' attitudes and behavior in maintaining the dental health of Joyosuran Kindergarten children. Method: Quasi-experimental research with one group pre-post test method. The sample is 38 people with total sampling method. The variables observed were changes in knowledge, attitudes and actions of parents before and after counseling. The data were tested with the Wilcoxon and Sommer d'gamma tests. Results: The results of the Wilcoxon test showed that there was a significant difference (p=0.000) between knowledge, attitudes and pre- and posttest actions with better post-test scores, while the Sommer d'gamma test results stated that there was no significant relationship between knowledge and attitudes (p sommer= p gamma=0.491), as well as knowledge and action (p sommer=p gamma = 0.686) (pre-test) of parents in maintaining children's oral and dental health. Conclusion: There are significant differences between the knowledge, attitudes and actions of pre- and post-intervention parents of Aisyiyah Joyosuran Kindergarten students.